ANALISIS RISIKO KESELAMATAN DAN KESEHATAN KERJA PADA PEKERJAAN JOINT MV PANEL DI PT XYZ - Ahmad Rizal Fathurrohman; Ganda Sirait (Computer Science and Industrial Engineering, 2024)
PT XYZ is a company engaged in Industry and provider of business areas and business support facilities. One of the facilities provided by PT XYZ is power plant construction. In power plant construction there are various types of work, one of which is the joint Medium Voltage (MV) panel process. The problem that occurs in this study is that there are cases of work accidents that occur in the Joint mv panel process so that it is necessary to control K3 risks to prevent work accidents. The purpose of this study is to identify potential hazards and make control efforts to reduce the level of risk of hazards in joint mv panel work. The method used in this research is HIRADC (Hazard Identification and Risk Assessment Determining Control). The results of this study obtained a decrease in risk levels after control, where there are 2 jobs (29%) with extreme risk categories and 5 jobs (71%) with high-risk categories and no jobs with moderate and low risk levels. However, after controlling, there are no more jobs with extreme risk and high-risk levels, there are only 2 jobs (29%) with moderate risk and 5 jobs (71%) with low risk. Proposals given to carry out risk control are through affirming the work system and field work flow standards, improving the system, improving the control system through administration, developing human resources and improving the control system through engineering and PPE.